2009
DOI: 10.3168/jds.2009-2135
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dystocia on the dry matter intake and behavior of Holstein cows

Abstract: Dairy cows that have a difficult calf delivery (dystocia) are more likely to develop health complications after calving, reducing productivity and welfare. Understanding the behavioral cues of dystocia may facilitate prompt obstetric assistance and reduce the long-term effect of the challenging delivery. The aim of this study was to describe the effects of dystocia on dairy cow behavior during the period around calving and to assess the use of these behaviors as potential indicators of dystocia. Individual dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
5
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 21 publications
6
85
5
2
Order By: Relevance
“…These results are also in agreement with Proudfoot et al (2009), who described decreases of approximately 36 and 50%, respectively, in the 24 h before and after calving, compared with 2 d before calving. Miedema et al (2011) monitored time spent feeding (summarized in 6-h periods) during the day of calving and found a decrease in the 6 h before calving compared with the same time periods on the day before calving.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…These results are also in agreement with Proudfoot et al (2009), who described decreases of approximately 36 and 50%, respectively, in the 24 h before and after calving, compared with 2 d before calving. Miedema et al (2011) monitored time spent feeding (summarized in 6-h periods) during the day of calving and found a decrease in the 6 h before calving compared with the same time periods on the day before calving.…”
supporting
confidence: 93%
“…We observed a tendency for DMI to decrease in the 24 h before calving by 24% compared with 2 to 4 d before calving; this decrease was primarily observed within 8 h of calving. Similarly, Proudfoot et al (2009) found that DMI decreased 32% in the 24 h before calving compared with 2 d before calving. Bertics et al (1992) reported a DMI decrease of 28% in the week precalving compared with a baseline recorded at 3 wk before calving.…”
mentioning
confidence: 74%
“…Svensson (2006) hypothesized that the association between reproductive disorders and CM could be due to a common factor affecting both disease complexes. Based on the conclusions of Proudfoot et al (2009), who showed that cows with dystocia had reduced DMI and water intake 24 h before calving, a more pronounced negative energy balance in heifers that needed assistance and decreased weakened immunity could possibly explain this finding. Still, it does not explain why this factor was not associated with IMI with major pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural indications of discomfort are present even before parturition. For example, after parturition, dystocic cows showed less dry matter and water intake and more transitions from standing to lying (Proudfoot et al, 2009). While the duration of calving is not different, more contractions occur in assisted calving and the cows are more restless and raise the tail for longer (Barrier et al, 2012b).…”
Section: Impact Of Reproductive Disorders (Dystocia and Metritis)mentioning
confidence: 99%